1982
DOI: 10.1093/infdis/145.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Cholera-Like Illness Due to Aeromonas sobria

Abstract: A Thai woman from Bangkok was admitted to a hospital in Paris for a cholera-like illness. A culture of her "rice-water" diarrhea was negative for Vibrio cholerae and enterotoxigenic Escherichia coli but was positive for Aeromonas sobria. This strain produced enterotoxin, cytolysin, proteolysin, hemolysin, and a cell-rounding factor. Acute -and convalescent-phase sera showed an increase in neutralizing antibodies to enterotoxin, cytolysin, and hemolysin. The enterotoxin, which was labile at 100 C, induced an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Among the motile aeromonads, A. hydrophila and A. sobria have been associated with human illness (7,8,13) . The present study revealed that A. caviae was predominant, comprising 43%, followed by A. sobria (35%) and A. hydrophila (20%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the motile aeromonads, A. hydrophila and A. sobria have been associated with human illness (7,8,13) . The present study revealed that A. caviae was predominant, comprising 43%, followed by A. sobria (35%) and A. hydrophila (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Ashida River flows through rural, suburban (stations 1, 2; upper region), and urban areas (stations 3, 4; lower region) of the east portion of Hiroshima Prefecture and shed into the Seto Inland Sea (stations 6 to 8; marine) with a total length of about 90 km. Station 5 is located in a branch stream, Takaya River, which is highly polluted and sheds the effluents of the slaughter house situated in its upstream along with the domestic discharges into Ashida River (5) ; and Seto Inland Sea (6)(7)(8) …”
Section: Methodsmentioning
confidence: 99%
“…On extremely rare occasions, Aeromonas has been linked to cholera-like disease (138). The most definitive example of such infections is a case report by Champsaur et al (34) describing cholera-like disease with "rice-water" stools in a 67-year-old Thai woman. During the first 2 days of infection, the patient lost 13 liters of "rice-water" stools and received 21 liters of intravenous fluids (saline and plasma) in an attempt to return her to normal electrolyte status.…”
Section: Aeromonas and Gastroenteritismentioning
confidence: 99%
“…Individual species of Aeromonas have been associated with particular clinical syndromes, the frequency of which varies geographically and seasonally (Champsaur et al, 1982;; however, reports on individual species remain sparse. Certain strains of Aeromonas produce an enterotoxin (Sanyal et al, 1975), and this factor is reported to be highly associated with certain biochemical characteristics Turnbull et al, 1984).…”
Section: Introductionmentioning
confidence: 99%